Why Fast Trains Work: An Assessment of a Fast Regional Rail System in Perth, Australia - McIntosh, J.; Newman, Peter; Glazebrook, G. (Scientific Research Publishing, 2013)
Perth’s new 72 km long Southern Rail System opened in 2007. With a maximum speed of 137 km/hr and an average speed of almost 90 km/hr this system acts more like a new high speed rail than a suburban rail system, which in Australia typically averages around 40 km/hr for an all-stops services. The Southern Rail Line was very controversial when being planned as the urban areas served are not at all typical of those normally provided with rail but instead were highly car dependent and scattered low density land uses. Nevertheless it has been remarkably successful, carrying over 70,000 people per day (five times the patronage on the express buses it replaced) and has reached the patronage levels predicted for 2021 a decade ahead of time. The reasons for this success are analyzed and include well-designed interchanges, careful integration of bus services, the use of integrated ticketing and fares without transfer penalties and, crucially the high speed of the system when compared to competing car based trips. The Southern Rail Line in effect explodes the current paradigm of transfer penalties, exposing this as a myth. The lessons for transport planning in low density cities are significant, and are explored further in the paper.